Mental health and well‐being of Aboriginal and Torres Strait Islander peoples in Australia during COVID‐19. Issue 4 (20th September 2021) - Dudgeon, Pat; Alexi, Joanna; Derry, Kate; Brideson, Tom; Calma, Tom; Darwin, Leilani; Gray, Paul; Hirvonen, Tanja; McPhee, Rob; Milroy, Helen; Milroy, Jill; Murray, Donna; et al.
Abstract: In May 2020, an independent working party was convened to determine the mental health and well‐being needs of Aboriginal and Torres Strait Islander peoples in Australia, in response to COVID‐19. Thirty Aboriginal and Torres Strait Islander leaders and allies worked together in a two‐month virtual collaboration process. Here, we provide the working party's five key recommendations and highlight the evidence supporting these proposals. Aboriginal and Torres Strait Islander self‐determination and governance must be prioritised to manage the COVID‐19 recovery in Aboriginal and Torres Strait Islander communities. To mitigate long‐term social and economic impacts of COVID‐19 to Australian society, the historical underinvestment in Aboriginal and Torres Strait Islander peoples must be reconciled. Equitable, needs‐based funding is required to support strengths‐based, place‐based initiatives that address the determinants of health. This includes workforce and infrastructure development and effective evaluation. There is a clear, informed pathway to health and healing for Aboriginal and Torres Strait Islander peoples being enacted by Aboriginal and Torres Strait Islander leadership and community organisations; it remains to be seen how these recommendations will be implemented.